UNIT 1.2 Fluidics. Issue 1 (July 2013) - Austin Suthanthiraraj, Pearlson P.; Graves, Steven W.
Abstract: The use of fluidics is implicit in a technology named "flow cytometry, " which flows a cell or particle through a sensing volume to obtain serial analysis of particles on a one by one basis. This flow of particles enables flow cytometry to collect information on multiple particle populations, giving it a distinct advantage over bulk analysis approaches. Moreover, flow cytometers can analyze thousands of particles per second in a single flowing stream. Additionally, use of volumetric sample delivery makes it possible for flow cytometers to accurately count cells and particles. Furthermore, the analysis results can be coupled with a fluidic diversion mechanism to sort and collect particles based on desired properties. Finally, when high‐throughput sampling technologies are employed to rapidly change the input of the sample stream, a flow cytometer can become an integral tool for high‐throughput screening. The above properties have made flow cytometry useful in a wide range of biomedical applications. In this unit we will present an overview of fluidic systems that make flow cytometry possible. This will introduce historical approaches, explanations of the commonly implemented current fluidics, and brief discussions of potential future fluidics where appropriate. Curr. Protoc. Cytom. 65:1.2.1‐1.2.14. © 2013 by John Wiley & Sons, Inc.